2019
DOI: 10.3390/nu11040892
|View full text |Cite
|
Sign up to set email alerts
|

Specific Collagen Peptides in Combination with Resistance Training Improve Body Composition and Regional Muscle Strength in Premenopausal Women: A Randomized Controlled Trial

Abstract: The aim was to investigate the effects of resistance exercise combined with supplementation of specific collagen peptides (SCP) on body composition and muscle strength in premenopausal women. In a double-blind, placebo-controlled, randomized trial 77 premenopausal women completed a 12-week resistance training (3 day/week) and ingested 15 g of SCP or placebo on a daily basis. Changes in body composition were determined by bioelectrical impedance analysis (BIA) and muscular strength by isometric strength testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(105 citation statements)
references
References 55 publications
6
94
3
2
Order By: Relevance
“…Zdzieblik et al [11] found higher FFM in their CP supplementation group compared with controls in a men’s cohort. This has been confirmed in another recent study that shows the same positive changes in FFM of their CP supplementing group compared to their placebo group in a women’s cohort [36]. The FFM includes passive as well as active contractile tissues [10,37].…”
Section: Discussionsupporting
confidence: 55%
“…Zdzieblik et al [11] found higher FFM in their CP supplementation group compared with controls in a men’s cohort. This has been confirmed in another recent study that shows the same positive changes in FFM of their CP supplementing group compared to their placebo group in a women’s cohort [36]. The FFM includes passive as well as active contractile tissues [10,37].…”
Section: Discussionsupporting
confidence: 55%
“…When compared to both the minimum RDAs [30] and the actual dietary protein intakes for both men and women in absolute values [33], the effective daily amounts of functional collagen peptides (2.5 to 15 g) observed in the literature [6,7,8,9,10,11,12,13,14,15,16] were found to be below the maximum level of collagen that may be incorporated in the standard American diet (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Relative to total daily protein intakes, the effective amounts of functional collagen peptides observed in the literature (2.5 g to 15 g) were found to be below the maximum level of collagen that may be incorporated as protein substitution in diets meeting the minimum RDAs for protein [6,7,8,9,10,11,12,13,14,15,16]. In practice, the daily protein consumption in the standard American diet is above the RDA, having increased slightly over the 10-year period from 1999–2008, from 15.6% to 15.9% (100 g) in men, and from 15.2% to 15.5% (67 g) in women, relative to the total energy intake [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, similar intervention studies using potent and established nutritional (e.g., animal-derived protein [5]) and pharmacological (e.g., testosterone [133]) stimulators of muscle growth did not observe such marked increases in fat-free mass [134], leading some to question the findings of Zdzieblik et al [134]. More recently, Jendricke et al [135] also reported greater increases in fat-free mass and a greater decrease in fat mass following dietary collagen supplementation, supporting positive body composition changes in response to this form of supplement. In the absence of known mechanisms, it has been suggested that a reduction in adipocyte size may contribute to changes in fat mass [121], in addition to the already mentioned hypothesis of ECM adaptations contributing to fat-free mass gains.…”
Section: Skeletal Musclementioning
confidence: 96%